2019
DOI: 10.23938/assn.0642
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity amongst different diagnostic tools in frailty screening

Abstract: artículos originales0 Heterogeneidad en el cribado poblacional de la fragilidad Heterogeneity amongst different diagnostic tools in frailty screening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…The combination of multiple protocols for any evaluation decreased the risk of false negative occurrence (5) . By contrast, a recent study (27) showed that TUG was an effective tool in identifying frailty.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The combination of multiple protocols for any evaluation decreased the risk of false negative occurrence (5) . By contrast, a recent study (27) showed that TUG was an effective tool in identifying frailty.…”
Section: Discussionmentioning
confidence: 80%
“…The absence of a correlation between EFE and gender differ with research reviews that indicate that females are more prone to develop Frailty Syndrome (25,26) , as well as finding that elderly women presented a higher occurrence of weight loss, fatigue, muscle weakness and low level of physical activity (23) . Additionally, females are 3 to 4.6 times more likely to develop frailty when compared to males (27) . The results presented here differed from a study with a sample group made up exclusively of elderly women, finding a higher prevalence in the group classified as frail paired with a significant increase in the vulnerable condition (10) , also highlighting that frailty compromises quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ausência de correlação entre EFE e sexo discordou de revisões que apontaram que o sexo feminino está mais propenso ao desenvolvimento da Síndrome da Fragilidade (25,26) e foi demonstrado que idosas apresentaram maior frequência de perda de peso, fadiga, fraqueza muscular e baixo nível de atividade física (23) , ainda mais, de 3 a 4,6 vezes mais chances de desenvolver fragilidade quando comparado ao sexo masculino (27) . Os resultados aqui apresentados foram divergentes de estudo com uma amostra exclusivamente composta por idosas que apontou a prevalência maior na faixa classificada como frágil e um aumento importante na condição vulnerável (10) , e destacou que a fragilidade compromete a qualidade de vida.…”
Section: Discussionunclassified
“…Estudos (25,26) certificaram que idosos categorizados como não frágeis apresentaram tempo de execução no TUG menor que os de grupos frágeis ou pré-frágeis, e que foi consonante com os resultados aqui analisados.…”
Section: Discussionunclassified